Legal Framework of Employing Autonomous Navigation Technologies in Maritime Transport Vessels: Challenges and Benefits from Stakeholder Perspectives - Abdelhady, Mahmoud Abd Elgawwad (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2024)
The study aims to explore the challenges of employing autonomous navigation technologies in maritime transport vessels by identifying the main challenges and assessing their relation to the readiness of the legislative framework. The methodology conducted for this study is semi-structured interviews to collect data, and participants were recruited via snowball sampling. This method was a series of one-on-one, open-ended interviews with a variety of stakeholders involved in maritime transportation, including